2010
DOI: 10.1038/nmat2914
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature, high-performance solution-processed metal oxide thin-film transistors formed by a ‘sol–gel on chip’ process

Abstract: At present there is no ‘ideal’ thin-film transistor technology for demanding display applications, such as organic light-emitting diode displays, that allows combining the low-temperature, solution-processability offered by organic semiconductors with the high level of performance achievable with microcrystalline silicon1. N-type amorphous mixed metal oxide semiconductors, such as ternary oxides Mx1My2Oz, where M1 and M2 are metals such as In, Ga, Sn, or Zn, have recently gained momentum because of their high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
829
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 981 publications
(850 citation statements)
references
References 25 publications
20
829
1
Order By: Relevance
“…Unlike conventional a‐IGZO TFTs,45, 46 here we use binary metal oxides for each layer in the stacked structures. This strategy helps to avoid complex and in some cases unwanted chemical interactions between different precursor molecules that are generally known to degrade the electrical performance of solution‐processed oxide TFTs 4, 30, 47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike conventional a‐IGZO TFTs,45, 46 here we use binary metal oxides for each layer in the stacked structures. This strategy helps to avoid complex and in some cases unwanted chemical interactions between different precursor molecules that are generally known to degrade the electrical performance of solution‐processed oxide TFTs 4, 30, 47…”
Section: Resultsmentioning
confidence: 99%
“…Because of the latter requirement it is not a trivial question whether high‐quality oxide heterointerfaces can be realized using simpler, cost‐efficient, and high‐throughput fabrication methods that are compatible with existing semiconductor fabrication processes (e.g., solution‐based) and even perhaps temperature‐sensitive substrate materials such as plastic. Thus, the development of ease to implement metal oxide hetero/multilayer structures could help overcoming important bottlenecks associated with the level of performance and manufacturing of incumbent TFT technologies, and enable the emergence of a host of large‐area, flexible optoelectronics 4, 26, 27, 28, 29, 30…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] A few studies on low-temperatureprocessable MOSs have been reported. [13][14][15][16] However, the authors of these studies used either complex and unstable precursors that required significant effort and multiple steps for synthesis or complicated chemical reactions that are not appropriate for the general fabrication technique. Although methods based on nanostructures, nanoparticles, nanorods or carbon-related materials also allow low-temperature deposition, concerns about the uniformity of the resulting devices related to the uncontrollable distribution of nanosized materials still remain.…”
Section: Introductionmentioning
confidence: 99%
“…The O 1s peak at higher binding energy (532.0 eV) is associated with chemisorbed or dissociated oxygen or OH species, such as adsorbed H 2 O or O 2 adsorbed on the surface of the materials. 34 In particular, absorption of water on the surface of the air cathode results in an undesirable effect in Li-O 2 batteries. 35 The content of oxygen vacancies in the C/Fe 3 O 4 HGs was higher than that in the Fe 2 O 3 HGs.…”
Section: Resultsmentioning
confidence: 99%